Kedudukan Hukum Badan Bank Tanah Dalam Pengadaan Tanah Untuk Kepentingan Umum - Rahadiyan Veda Mahardika; Gatot Suyanto (Faculty of Law, University of Jember, Indonesia, 2022)
The provisions in the Omnibus Law of the Job Creation Law Number 11 of 2020 regulates one of them regarding land. This land regulates the authority of the state in regulating the designation, use and management of land which is manifested by the Government Regulation Number 64 of 2021 concerning the Land Bank Agency. The Land Bank Agency has the authority to prepare master plans, help provide ease of Business Licensing/approval, carry out land acquisition, and determine service rates. In practice, Land Banks generally have advantages and disadvantages that have an impact on national land law. This study uses a normative juridical method with a statutory approach and a conceptual approach, and legal materials are analyzed using a deductive method. This study aims to describe and explain the Land Bank regulation in the Job Creation Act and the Government Regulation concerning the Land Bank Agency and the implications for the national land law. The result of this research is the arrangements related to the land bank need to be amended to reinforce its authority as land management, especially overlapping authorities with the National Land Agency. It is also necessary to have clear, comprehensive and just legal instruments in which every activity carried out must meet the elements of openness and community participation to prevent abuse of authority from the Land Bank Agency. KEYWORDS: Land Bank, Job Creation Law, Indonesian Land Law